2009
DOI: 10.1016/j.jacc.2008.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Single Coronary Artery

Abstract: A s part of the workup for pulmonary hypertension, a 59-year-old man underwent coronary angiography. This demonstrated a single coronary artery arising from the right sinus of valsalva, which gave off 3 branches that supplied the entire left ventricle. Left ventricular function was normal by ventriculography. Angiography is often sufficient to define coronary anomalies; however, we found coronary computed tomography angiography useful to confirm this anomaly.Single coronary artery anomaly is rare, with inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…As an isolated finding it occurs in approximately 0.024% to 0.066% of the population. In association with certain other congenital anomalies, however, it is found considerably more frequently; the incidence in a series of 54 cases of persistent truncus arteriosus was 18.5% and in another paper it was reported to be 18% 4 ; in a study of coronary angiograms of 296 patients with Tetralogy of Fallot a single coronary artery was found in seven cases and in pulmonary atresia the incidence is around 17%. 2 In 1979, Lipton et al proposed a very useful angiographic classification'1', further modified in 1990 by Yamanaka and Hobbs.…”
Section: Discussionmentioning
confidence: 95%
“…As an isolated finding it occurs in approximately 0.024% to 0.066% of the population. In association with certain other congenital anomalies, however, it is found considerably more frequently; the incidence in a series of 54 cases of persistent truncus arteriosus was 18.5% and in another paper it was reported to be 18% 4 ; in a study of coronary angiograms of 296 patients with Tetralogy of Fallot a single coronary artery was found in seven cases and in pulmonary atresia the incidence is around 17%. 2 In 1979, Lipton et al proposed a very useful angiographic classification'1', further modified in 1990 by Yamanaka and Hobbs.…”
Section: Discussionmentioning
confidence: 95%
“…After performing autopsy, it was found that the athlete had single coronary artery arising from right sinus of Valsalva. [ 5 ] Among the diverse presentation of coronary anomaly, single coronary anomaly is an important rare anomaly that has been frequently associated with sudden death. There have been controversies regarding the prognosis following medical treatment or surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from routine checkup for cardiovascular system, such as ECG, echocardiography, treadmill test, and others, we can particularly perform ventriculography to assess the functioning of ventricles which frequently comes out to be normal. [ 5 ] After determining the anomaly, the recent advancement of diagnostic techniques such as multislice CT and 3D construction if images are highly recommended to evaluate and confirm the subtypes and definitive anomaly that is present in a patient. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Because of its rarity there are currently no guidelines on the management of patients with SCA. Revascularization is indicated in cases of atherosclerotic CAD and ischemia [ 11 ]. Invasive management strategies in patients with SCA and atherosclerotic CAD are very rare and pose high risk since cannulation of common trunk by large catheter might be poorly tolerated given the fact that the whole heart gets its supply from that common single trunk [ 12 ].…”
Section: Discussionmentioning
confidence: 99%